Gregory the Great's Metaphor of the Physician of the Heart as a Model for Pastoral Identity - McGrath-Merkle, Clare (Journal of religion and health, 2011)
The identity of the Roman Catholic priesthood remains in serious crisis. Scholars have called for a return to traditional sources to find possible solutions, including the Early Church Fathers and the Hebrew Bible. Following Oden, this article further explores Pope Gregory the Great's The Book of Pastoral Rule and his ideals regarding pastoral identity. Of unique importance is his notion of the pastor as a "physician of the heart," unrecognized previously as central to his project.